The book of Bill - Hirsch, Alex, 1985- (Hyperion Avenue, 2024)
"Bill Cipher, the demon that terrorized Gravity Falls, is back to tell his side of the story. Inside this book, Bill sheds light on his bizarre origins, his sinister effects on human history, the Pines family's most embarrassing secrets, and the key to overthrowing the world (laid out in a handy step-by-step guide). This chaotic and beautifully illustrated tome contains baffling riddles, uncrackable ciphers, lost Journal 3 pages, ways to cheat death, the meaning of life, and a whole chapter on Silly Straws. But most importantly, 'The Book of Bill' is deeply, deeply cursed." --